Thursday

March 5, 2015

March 5, 2015

Posted by **Ryan** on Monday, January 16, 2012 at 9:14am.

- math -
**Reiny**, Monday, January 16, 2012 at 9:18amp(x) = 2x^4 - 3x^3 + 5x^2 - 1

p(4) = 2(4^4) - 3(4^3) + 5(4^2) - 1

= 2(256) - 3(64) + 5(16) - 1

= 512 - 192 + 80 - 1

= 399

**Answer this Question**

**Related Questions**

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - What is P(-4) given that P(x) = 2x to the fourth power - 3x to the third ...

math - 1. unite similar terms with parenthesis. x=2 y=-3 and z=5 find the value ...

Algebra - I am so confused with the rules of exponents. I know them, but I have ...

Math 8R - Help!!!!!!!! - The expression 2(8a to the 2nd power + a - 1) + 3(a + 3...

Algebra - Factor each of following expressions x (4th power) - x (3rd power) - ...

Algebra - I'm not sure if anyone saw my question yesterday, but here it is again...

math - The question that have is to simplify and write the answer in ...

Math/Standard and scientific notation - Express each measure in standard form. (...